2019
DOI: 10.1098/rsta.2018.0398
|View full text |Cite
|
Sign up to set email alerts
|

Lightning and charge processes in brown dwarf and exoplanet atmospheres

Abstract: The study of the composition of brown dwarf atmospheres helped to understand their formation and evolution. Similarly, the study of exoplanet atmospheres is expected to constrain their formation and evolutionary states. We use results from three-dimensional simulations, kinetic cloud formation and kinetic ion-neutral chemistry to investigate ionization processes that will affect their atmosphere chemistry: the dayside of super-hot Jupiters is dominated by atomic hydrogen, and not H 2 O.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 89 publications
3
32
0
1
Order By: Relevance
“…The study of hot Jupiters atmospheres has revealed a broad composition and structural diversity in gas-rich planets (Jensen et al 2012;Sing et al 2012;Crossfield 2015;Deming & Seager 2017;Madhusudhan et al 2016). When these planets are under extreme conditions, in particular, located very close to their host stars and consequently being strongly irradiated, their temperatures increase and lead to different atmospheric chemistry between the day and night-sides of atmosphere (Arcangeli et al 2018;Bell & Cowan 2018;Helling & Rimmer 2019) in comparison with cooler planets. This creates a new type of exoplanet called ultra-hot Jupiters (hereafter UHJ).…”
Section: Introductionmentioning
confidence: 99%
“…The study of hot Jupiters atmospheres has revealed a broad composition and structural diversity in gas-rich planets (Jensen et al 2012;Sing et al 2012;Crossfield 2015;Deming & Seager 2017;Madhusudhan et al 2016). When these planets are under extreme conditions, in particular, located very close to their host stars and consequently being strongly irradiated, their temperatures increase and lead to different atmospheric chemistry between the day and night-sides of atmosphere (Arcangeli et al 2018;Bell & Cowan 2018;Helling & Rimmer 2019) in comparison with cooler planets. This creates a new type of exoplanet called ultra-hot Jupiters (hereafter UHJ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent laboratory experiments by Bourgalais et al (2020) suggest the H3O + is likely to be both the dominant and the most easily observed molecular ions in sub Neptune exoplanets; Bourgalais et al (2020) also suggest that H3O + should be observable by forthcoming exoplanet characterisation space missions, such a detection would require a reliable line list for hot H3O + . Helling & Rimmer (2019) suggest that H3O + should be detectable in free-floating brown dwarfs and super-hot giants.…”
Section: Introductionmentioning
confidence: 94%
“…As well as the Solar System's giant planets, there is now considerable interest in determining the composition of giant exoplanet atmospheres and those of cool stars. Recently Helling & Rimmer (2019) have discussed the possibility of detecting H3O + in exoplanets and brown dwarf stars. They modelled the atmosphere of an M8.5 dwarf with an effective temperature of 2600 K. Their model indicated that the H3O + density is likely to be 10 11 m −3 throughout the pressure range from 1 bar to 1 µbar, and considerable proportion of the star's atmosphere.…”
Section: H3o + In Planetary Atmospheres and Cool Starsmentioning
confidence: 99%
“…HCN is furthermore suggested as spectral tracer for lightning events in planetary atmospheres. Knowing its background abundance may help to disentangle such lightning traces (Hodosán et al 2017;Helling & Rimmer 2019).…”
Section: H 2 O Abundance In the Equatorial And Terminator Regionsmentioning
confidence: 99%
“…It has been shown that turbulent and molecular diffusion, photochemical processes, as well as interaction with free electrons may alter the chemical composition of planetary atmospheres from thermochemical equilibrium to a disequilibrium chemistry state (see, e.g., Line et al 2010;Moses et al 2011;Venot et al 2012;Miguel & Kaltenegger 2013;Moses 2014;Rimmer & Helling 2016;Tsai et al 2017;Helling & Rimmer 2019). While previous studies have typically been conducted on colder planets, Kitzmann et al (2018) reported that the chemical state of the atmosphere of KELT-9b also deviates from thermochemical equilibrium at pressures lower than 1 mbar in a 1D setup.…”
Section: Introductionmentioning
confidence: 99%